Recommendation of affordable halal certification fee - Purwanto, Endi Hari; Anggraeni, Putty; Dewantoro, Auraga; Anggundari, Widia Citra; Tampubolon, Biatna Dulbert (Halal Studies and Society, 2024)
Halal certificates protect consumers from foods that do not comply with Islamic Sharia, and Indonesia represents a significant market for halal products, with certification being a key competitive factor in international trade. The response to halal certification varies, with some considering the fee affordable, while others view it as burdensome for businesses. Therefore, this study aimed to recommend affordable halal certification fee for small, medium, and large entrepreneurs. To achieve this objective, a survey method was used to target business actors, combined with literature reviews. A survey was conducted through questionnaires and interviews that included micro, small, medium, and large businesses. The affordable certification fee for micro and small business actors averaged IDR 774,231, with the highest being IDR 828,571. Meanwhile, for medium businesses, it ranged from IDR 1,166,667 to a high of IDR 2,030,769, and for large businesses, the average was IDR 2,995,581, with a maximum of IDR 5,214,286.